Pengaruh Investasi terhadap Pertumbuhan Ekonomi dan Penyerapan Tenaga Kerja Serta Kesejahteraan Masyarakat di Provinsi di Indonesia - Sulistiawati, Rini (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2012)
This study aims to examine and analyze the effect of investment on economic growth, labor absorption and social welfare at province in Indonesia. The study period was five years i.e. from 2006 to 2010 by using secondary data provided by Central Bureau of Statistics in the form of combination between times series data (from 2006 to 2010) and cross-sectional data (33 province in Indonesia) also known as panel data. Hypothesis testing in this study is conducted by using Path Analysis Model under SPSS 17.0. Test of 5 (five) hypothesis with level of significance Î±  =  0.05  obtained the following results: First, investment has a negative but not significance effect on economic growth. Second, investment has a positive and significance effect on labor absorption. Third, economic growth has a positive but not significance effect on labor absorption. Fourth, economic growth has a positive but not significance effect on social welfare. Fifth, labor absorption has positive but not significance effect on social welfare.